Optimizing the Potential of Local Wisdom in Enriching Religious Moderation Practices: Collaborative KUKERTA for Community Empowerment - Muhammad; Muhammad Sugama Akbar; Indah Rahimah; Putri Puziasih; M. Ersan; Cici Safitri; Aulia Rahman; Siti Rosidah Astuti; Gusti Adinata; Ulfa Tamsila; Siti Zubaidah; Embun Sagita; Muhammad Safi’i; Nurhadijah Nurhadijah; Sari Azhari; Raja Nur Fazlina; Rahman; Reza Maulana; Khozinul Asror (Unram Journal of Community Service, 2025)
The Collaborative Community Service Program (Kuliah Kerja Nyata/ KKN) across multidisciplinary study programs serves as a strategic model for strengthen-ing religious moderation based on local wisdom and community empowerment. This service program was implemented in Senyerang Village, Senyerang District, Tanjung Jabung Barat Regency, involving students from five study programs: Is-lamic Religious Education (PAI), Islamic Communication and Broadcasting (KPI), Constitutional Law (HTN), Sharia Economics (ESY), and Sharia Business Management (MBS). The program focused on enhancing community capacity through the following activities: (1) teaching and strengthening religious moderation values, (2) producing documentary films highlighting local wisdom and toler-ance, (3) legal socialization on anti-bullying and anti-drug awareness, (4) halal cer-tification training, and (5) assistance in creating online marketing accounts for local products. The results indicate significant improvements in the community’s understanding of religious moderation values, legal awareness, and digital marketing skills among local entrepreneurs, as well as the establishment of a halal based economic network rooted in local wisdom. This collaborative KKN program provides substantial contributions to the social, cultural, and economic development of the Senyerang community.